Tradisi Upacara Perkawinan Adat Pandhebeh Perspektif Hukum Islam (Studi Kasus Desa Wringin Kecamatan Wringin Kabupaten Bondowoso) - Dimas Adityarahman (Rechtenstudent, 2021)
The Pandhebeh tradition is a legacy that must be preserved and approved, although this tradition originated from Madura. But according to some religious leaders say the tradition of this pandhebeh is for the community's efforts towards God to oppose the coming of all bad things that will happen. The focus of the problem examined in this paper is 1. How is the tradition of the traditional Pandhebeh marriage ceremony in the community of Wringin Village, Wringin District, Bondowoso Regency? 2. How about a review of Islamic law about the traditional ceremonial tradition of Pandhebeh marriage in Wringin Village, Wringin District, Bondowoso Regency? The research approach used in this study is qualitative research with the type of field research. From this study, we concluded: first, The tradition of Pandhebeh rocket in Wringin Village is a hereditary tradition with the aim of eliminating the bad luck inherent in Pandhebeh children. Second, According to the scholars of ushul fiqh that adat or ‘urf which is a habit that lives in the legal community may be as long as there is no text that prohibits it. So the pandhebeh traditional wedding ceremony tradition in the village of Wringin we review through ‘urf, the researchers categorize this tradition including‘ urf al-shohih, where this tradition can be accepted by the community